Mischaracterizing social psychology to support the laudable goal of increasing its political diversity. (8th September 2015) - Eagly, Alice H.
Abstract: Duarte et al.'s arguments for increasing political diversity in social psychology are based on mischaracterizations of social psychology as fundamentally flawed in understanding stereotype accuracy and the effects of attitudes on information processing. I correct their misunderstandings while agreeing with their view that political diversity, along with other forms of diversity, stands to benefit social psychology.